2010
DOI: 10.1001/archgenpsychiatry.2010.175
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Interneurons in Bipolar Disorder

Abstract: Context Postmortem studies have reported decreased density and decreased gene expression of hippocampal interneurons in bipolar disorder, but neuroimaging studies of hippocampal volume and function have been inconclusive. Objective To assess hippocampal volume, neuron number and interneurons in the same specimens of bipolar and healthy control subjects. Design Whole human hippocampi of 14 bipolar and 18 healthy control subjects were cut at 2.5 mm intervals and sections from each tissue block were either Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
98
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 77 publications
7
98
0
1
Order By: Relevance
“…In keeping with previous literature, the 2D-DIGE method identified reductions in the expression of hippocampal of parvalbumin (PVALB) in both diagnostic groups, (Konradi et al, 2011a;Konradi et al, 2011b;Schmidt and Mirnics, 2014).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In keeping with previous literature, the 2D-DIGE method identified reductions in the expression of hippocampal of parvalbumin (PVALB) in both diagnostic groups, (Konradi et al, 2011a;Konradi et al, 2011b;Schmidt and Mirnics, 2014).…”
Section: Discussionsupporting
confidence: 82%
“…While some findings are similar for both disorders (Haukvik et al, 2014;Mathew et al, 2014), differences are described in the overall extent and in the premorbid manifestation of hippocampal volume reductions (Ellison-Wright and Bullmore, 2010;Fornito et al, 2009;Fusar-Poli et al, 2011;Fusar-Poli et al, 2012), which may relate to different underlying biological mechanisms (Bellivier et al, 2013). At the histological and cellular level, several studies have found hippocampal neurons of compromised morphology and organization, as well as pre-synaptic and dendritic deficits, in schizophrenia (Harrison, 2004) and bipolar disorder (Konradi et al, 2011b). Amongst the neuron populations affected by these changes, GABAergic interneurons, and particularly those of the fast-spiking basket-and chandelier type, have come into the focus in schizophrenia and bipolar disorder research, mainly because of solid evidence for widespread reductions in the concentration of proteins typically expressed by fast-spiking cells such as GAD67, somatostatin, and parvalbumin (Lewis et al, 2005;Woo et al, 1997) in several cortical regions (Hashimoto et al, 2008).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the hippocampal CA3 region of DGKβ KO mice, the number of parvalbumin-positive cells was decreased (vs. WT controls), which would increase the susceptibility of DGKβ KO mice to seizure. Interestingly, the number of parvalbumin positive interneuron is decreased in the hippocampus of patients with bipolar disorder, too [11,21,22]. We reported ealier that DGKβ KO mice display mania-like behavior [8], and others have reported that a splice variant at the COOH-terminal of DGKβ is related to bipolar disorder [23].…”
Section: Discussionmentioning
confidence: 65%
“…Postmortem studies have demonstrated smaller pyramidal neuron cell bodies (13,14), reduced dendritic spine density (15), and reduced interneuron density and number (16)(17)(18) in the hippocampi of patients with schizophrenia and bipolar disorder. The postmortem cellular findings differ among subfields, with CA4 showing more prominent pyramidal soma reduction than CA1 in patients with schizophrenia (16) and CA3 showing decreased number of mossy fiber synapses in patients with schizophrenia (15) as well as a significant reduction of somatostatin-positive neurons in CA1 and parvalbumin-positive neurons in CA1 and CA4 in patients with bipolar disorder (17). Although postmortem hippocampal neuronal abnormalities are present in both patients with schizophrenia and patients with bipolar disorder, there is evidence of diagnostically specific differences in presubiculum-patients with schizophrenia show reduced somatostatinpositive neuron density compared with patients with bipolar disorder (18).…”
mentioning
confidence: 99%